Blockchain technology and applications for digital marketing - Bansal, Rohit, 1982-; Malyadri, Pacha, 1958-; Singh, Amandeep, 1982-; Pervez, Asif, 1988- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"The main objective of the book is to provide insights on the blockchain technology and its applications in digital marketing to allow professionals and researchers gain comprehensive understanding of how this technology can influence the future of the digital marketing industry"--